WHEAT LEAF RUST (PUCCINIA TRITICINA) REACTIONS OF HOBBIT ‘‘SIB’’/BEZOSTAJA SUBSTITUTION LINES - . Abdul, S. D (Emirates Journal of Food and Agriculture, 2011)
The wheat leaf rust reaction resulting from the substitution of individual chromosomes of the wheat cultivar Hobbit ?sib' with their homologues from Bezostaja were investigated using isolate WBRP 85-31, that is avirulent on both cultivars in the glasshouse and the field. Seedlings of most lines had low infection types (ITs), except the line with chromosome substitution 7A that had IT 3-. Significant decreases in leaf area infected were observed on substitution lines with chromosomes 2D, 5D and 5BL/7BL, whereas the substitution line with chromosome 1B had a significant increase in the level of infection as compared with that on Hobbit ?sib'. This provided a means of identifying chromosomes with resistance genes against leaf rust disease that can be transferred to cultivated lines for the control of the disease.